Small Molecule DFPM Derivative-Activated Plant Resistance Protein Signaling in Roots Is Unaffected by EDS1 Subcellular Targeting Signal and Chemical Genetic Isolation of victr R-Protein Mutants. - Hans-Henning Kunz; Jiyoung Park; Emily Mevers; Ana V García; Samantha Highhouse; William H Gerwick; Jane E Parker; Julian I Schroeder (PLoS ONE)
The small molecule DFPM ([5-(3,4-dichlorophenyl)furan-2-yl]-piperidine-1-ylmethanethione) was recently shown to trigger signal transduction via early effector-triggered immunity signaling genes including EDS1 and PAD4 in Arabidopsis thaliana accession Col-0. Chemical genetic analyses of A. thaliana natural variants identified the plant Resistance protein-like Toll/Interleukin1 Receptor (TIR)-Nucleotide Binding (NB)-Leucine-Rich Repeat (LRR) protein VICTR as required for DFPM-mediated root growth arrest. Here a chemical genetic screen for mutants which disrupt DFPM-mediated root growth arrest in the Col-0 accession identified new mutant alleles of the TIR-NB-LRR gene VICTR. One allele, victr-6, carries a Gly216-to-Asp mutation in the Walker A domain supporting an important function of the VICTR nucleotide binding domain in DFPM responses consistent with VICTR acting as a canonical Resistance protein. The essential nucleo-cytoplasmic regulator of TIR-NB-LRR-mediated effector-triggered immunity, EDS1, was reported to have both nuclear and cytoplasmic actions in pathogen resistance. DFPM was used to investigate the requirements for subcellular EDS1 localization in DFPM-mediated root growth arrest. EDS1-YFP fusions engineered to localize mainly in the cytoplasm or the nucleus by tagging with a nuclear export signal (NES) or a nuclear localization signal (NLS), respectively, were tested. We found that wild-type EDS1-YFP and both the NES and NLS-tagged EDS1 variants were induced by DFPM treatments and fully complemented eds1 mutant plants in root responses to DFPM, suggesting that enrichment of EDS1 in either compartment could confer DFPM-mediated root growth arrest. We further found that a light and O2-dependent modification of DFPM is necessary to mediate DFPM signaling in roots. Chemical analyses including Liquid Chromatography-Mass Spectrometry and High-Resolution Atmospheric Pressure Chemical Ionization Mass Spectrometry identified a DFPM modification product that is likely responsible for bioactivity mediating root growth arrest. We propose a chemical structure of this product and a possible reaction mechanism for DFPM modification.